PENGARUH PEMBERIAN DIAZEPAM, FORMALIN & MINUMAN BERALKOHOL TERHADAP JUMLAH ERITROSIT DAN KADAR HEMOGLOBIN MENCIT Mus musculus L - Rahmawati, Huda; Tana, Silvana (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
This study aims to determine the influence of diazepam provision, formalin and alcoholic beverages on the number of erythrocytes and hemoglobin levels in mice Mus musculus L. The study was carried out with aklimasi 6 days and 30 days in thetreatment at Biology Laboratory Animal Structure and Function Department of Biology FMIPA UNDIP. Adult male mice was used that weigthing 25-30 gr. This experiment is performed with complete random design is divided into 3 treatment groups and 1 control group with 4 repetitions. Group P1 (0.04 mg diazepam), P2 (100ppm formalin), P3 (alcoholic beverages, alcohol content 4.8%) and controls (aquadest). BR2 feeding and drinking water ad libitum. Results of data analysis by giving diazepam, formalin and alcohol in mice showed no significant different in the number of erythrocytes and hemoglobin levels, in this case given the possibility of a substance capable of metabolized and excreted, so does not affect hematopoiesis and eritropoiesis.